PENINGKATAN KOMPETENSI PAEDAGOGIK GURU DALAM PENYUSUNAN PERENCANAAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI MADRASAH IBTIDAIYAH SWASTA TIMBANG LAWAN BOHOROK - Najmariah Najmariah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The writing of this School Action Research (PTS) was carried out by researchers of 9 educators (teachers) which consisted of 2 cycles by implementing the Improvement of Teacher's Pedagogical Competence in Preparing Learning Plans through Academic Supervision Can Improve the Quality of Teaching Teachers at Private Madrasah Ibtidaiyah Weigh Against Bohorok, The report on the results of the calculation of the Teacher's Learning Planning Ability about the initial correlation to the first cycle of 0.738 and the t test value of 4.283, as well as the calculation of the correlation of the first cycle to the second cycle of 0.921 and the t test value of 16.156 and the results of the calculation of the Learning Planning Component about the initial correlation to the first cycle of 0.713 and the value of the t test of 2.507, the calculation of the correlation between the first cycle and the second cycle is 0.875 and the t test value is 6.466. As well as the Improvement of Teacher's Pedagogical Competence in Preparing Learning Planning through Academic Supervision Getting Student Learning Outcomes at Private Madrasah Weigh Against Bohorok, with reports on the results of the calculation of the Average value of 9 Subjects about the initial correlation to the first cycle of 0.778 and the t-test value of 5.222 and calculations. The correlation between the first cycle and the second cycle is 0.934, and the t test value is 19.293. All calculation results show a significant value.Keywords: Teacher Pedagogic Competence, Learning Planning Compilation, Academic Supervision, Teacher Teaching Quality